2010
DOI: 10.3892/etm.2010.172
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and antiapoptotic effect of Asparagus racemosus root extracts in human lung epithelial H460 cells

Abstract: Abstract. the present study examined the antioxidant activity and protective effect of extracts from Asparagus racemosus roots against lipofectamine-induced apoptosis. Five fractions from a successive extraction process ranging from non-polar to more polar solvents were obtained. the total saponin content as a marker in terms of diosgenin equivalent value of the root extracts was found to be in the range of 240-420 µg/ mg extract, with higher values for the ethanol and aqueous fractions. the antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
(14 reference statements)
1
12
1
Order By: Relevance
“…This study showed that the scavenging ability, total phenolic compounds and total flavonoid contents of the ethanolic extract were higher than those from the aqueous extract but were four times lower than those reported from a methanolic extract. 2 The scavenging ability of the aqueous extract in this study was better than the study of Kongkaneramit et al 1 The previous study reported that the main components were saponins such as shatvarin, sarsapogenin and kaempferol. The presence of phenolic compounds is shown mostly via the antioxidant activities of plant sources.…”
Section: Discussioncontrasting
confidence: 60%
“…This study showed that the scavenging ability, total phenolic compounds and total flavonoid contents of the ethanolic extract were higher than those from the aqueous extract but were four times lower than those reported from a methanolic extract. 2 The scavenging ability of the aqueous extract in this study was better than the study of Kongkaneramit et al 1 The previous study reported that the main components were saponins such as shatvarin, sarsapogenin and kaempferol. The presence of phenolic compounds is shown mostly via the antioxidant activities of plant sources.…”
Section: Discussioncontrasting
confidence: 60%
“…Comprehensive fractionation of Thai A. racemosus was carried out by Kongkaneramit et al . () resulted in antioxidant activity (determined as DPPH radical scavenging activity and reported as EC 50 ) of aqueous and hydro‐alcoholic fractions that had EC 50 of 500–600 μg mL −1 which was much lower than that found with ascorbic acid (1.5 μg mL −1 ). A 70% methanol A. racemosus extract was fractioned by methanol, ethyl acetate, n‐Butanol, and water‐precipitated materials were examined for their antioxidant activities using DPPH radical scavenging activity (Acharya et al ., ).…”
Section: Phytochemistry Of Armentioning
confidence: 78%
“…The extracts of the roots of AR have in the last few years been determined to have a phytoestrogenic effect and help with neurodegenerative disorders, in addition to effects on antidiarrheal, antidyspepsia, adaptogenic, cardioprotective, antibacterial, immunoadjuvant and antitussive. 5 There are two major forms in which the root extracts of AR have been used (methanolic and aqueous extracts) as tablets, powders in tablets or a syrup form. 6 In addition, there have been reports of activities related to immunostimulant, antihepatotoxic or antioxytocic.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, there have been reports of activities related to immunostimulant, antihepatotoxic or antioxytocic. 5 In laboratory animals, there have been recent reports the extracts of AR roots have antioxidant and antidiarrheal effects. [7][8] In rats, the lipid peroxidation (malondialdehyde: MDA) decreased while there were increases in superoxide dismutase (SOD), catalase and ascorbic acid by the methanolic root extracts.…”
Section: Introductionmentioning
confidence: 99%